The evidence ex officio from the amendment of article 194 of the Civil Procedural Code - Hurtado Reyes, Martín Alejandro (2016)
With the presente article, the autor examines the trade test from the law amending No 30293. In this way, it analyzes the elements that comprise it: a) exceptionality trade test; b) test failure; c) source of evidence cited by legal parties; d) prohibition of supplying the parties of the burden of proof, e) contradiction assurance; f) contestability of the decision; g) trade test in second grade; and h) prohibition of nullity of sentence for lack of proof, under which concludes that the conditional use of the shaping trade, leaving aside the possibility of its arbitrary and indiscriminate use by the judge whose decision may be challenged if it does not comply with the above in order to maintain their duty of impartiality.